A survey on social network sites to determine requirements for learning networks for professional development of university staff. (14th July 2011) - Brouns, Francis; Berlanga, Adriana J.; Fetter, Sibren; Bitter-Rijpkema, Marlies E.; Bruggen, Jan; Sloep, Peter
Learning networks – online social networks where the learner is put central – are well suited for the non-formal professional development of academic staff. Our assumption is that learning networks can build on social network sites. Social network sites are becoming very popular and are very effective in connecting people, allowing exchange and sharing of all kinds of information and resources. Therefore, we designed a survey to explore the use and perception of social network sites among academic staff and to relate this to the functionalities required for learning networks for professional development. The survey results indicate that a learning network should cater for the desired social aspects along with facilities to organise and maintain resources and contacts.